2016
DOI: 10.17795/zjrms-6249
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Attentional Control and Resilience in Predicting the Rumination in Patients With Obsessive-Compulsive Disorder

Abstract: Background: Rumination is one of the extreme negative cognitions in patients with obsessive compulsive disorder (OCD). It is assumed that some cognitive problems such as attentional control can facilitate rumination and some internal capabilities such as resiliency can reduce engaging in these ruminations. Objectives: The present study investigated the relationship between rumination with attentional control and resiliency in patients with OCD. Patients and Methods: In this correlational study, 50 patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…Previous research has found that improving attentional control can also improve the ability to suppress worry-related thoughts and the control and prevention of rumination (Behzadpoor et al, 2016;Fox et al, 2015). Our findings suggest that cognitive training for the control of attention can be facilitated by conditions of high cognitive load, allowing individuals to inhibit involuntary attention to unwanted or threat-related distractors.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…Previous research has found that improving attentional control can also improve the ability to suppress worry-related thoughts and the control and prevention of rumination (Behzadpoor et al, 2016;Fox et al, 2015). Our findings suggest that cognitive training for the control of attention can be facilitated by conditions of high cognitive load, allowing individuals to inhibit involuntary attention to unwanted or threat-related distractors.…”
Section: Discussionmentioning
confidence: 48%
“…Literature on the neuropsychological functioning of OCD has been inconsistent and conflicting, as some studies suggest neurocognitive underperformance in attention, executive function, and memory, while others have not observed these deficits, after comparing with healthy undiagnosed individuals (Abramovitch & Cooperman, 2015;Fungueirino et al, 2020;Nakao et al, 2014). Furthermore, previous studies have shown self-reported attentional control deficits in OCD (Armstrong et al, 2011;Behzadpoor et al, 2016;Moradi et al, 2014). A study found that deficiency in attentional control increases rumination, or recurrent inner thoughts about a certain topic, in OCD patients (Behzadpoor et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 16 ] This self-report questionnaire consists of 20 items that assess attention control along two dimensions: attention focus, which pertains to the ability to sustain attention on a given task, and attention shifting, which refers to the ability to redirect attention to a new task or effectively engage in multitasking. The items are scored on a 4-point scale ranging from (1) “almost never” to (4) “always.” The scale has demonstrated satisfactory internal consistency reliability in the Iranian context, with Cronbach's alpha coefficient of 0.87[ 17 ] Moreover, the internal consistency reliability in this research was 0.88 and satisfactory. Both the content and construct validity of the scale have been confirmed through rigorous empirical examination by researchers.…”
Section: Methodsmentioning
confidence: 85%
“…Resilience is one of fundamental personality constructs and is involved in determining the individual's capability of withdrawing and resuming efforts to confront and cope with problems. Resilience is a complex process adopted by different individuals, groups, and communities in different social and cultural groups (18)(19)(20). Ahmadi et al (21) reported that academic resilience and procrastination predicted a tendency for substance abuse in secondary school students.…”
Section: Introductionmentioning
confidence: 99%